PENGADAAN TANAH UNTUK KEPENTINGAN UMUM IMPLIKASINYA DENGAN ALIH FUNGSI LAHAN DAN PENATAAN RUANG - Edy Lisdiyono (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2011)
The Land Procurement for public interest was unavoidable in the implementation of development due to population and industrial development.Transfer function of land from agricultural land was used for non-agricultural purposes, such as industrial areas or for residential / housing was increasing in every year. The reduction of agricultural land on the one hand bring benefits, but on the other hand can cause havoc if land use is not controlled properly and in accordance with the spatial planning, so there is zoning violations that not accordance with its designation, then both for licensing and user space, criminal sanctions should be applied in order to minimize land use.